2008
DOI: 10.1021/jp802920k
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes Decorated with Palladium Nanoparticles: Synthesis, Characterization, and Catalytic Activity

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 83 publications
3
69
0
1
Order By: Relevance
“…SDS is used as the surfactant and reducing agent in the synthesis of the Pd-graphene hybrids, since on heating it decomposes to 1-dodecanol which is subsequently oxidized to dodecanoic acid when it reduces the Pd(II) precursor to Pd [24]. As a result, the Pd-graphene hybrids have excellent dispersability, and no precipitation was observed after several months ( Fig.…”
Section: Synthesis Of Pd-graphene Hybridsmentioning
confidence: 99%
“…SDS is used as the surfactant and reducing agent in the synthesis of the Pd-graphene hybrids, since on heating it decomposes to 1-dodecanol which is subsequently oxidized to dodecanoic acid when it reduces the Pd(II) precursor to Pd [24]. As a result, the Pd-graphene hybrids have excellent dispersability, and no precipitation was observed after several months ( Fig.…”
Section: Synthesis Of Pd-graphene Hybridsmentioning
confidence: 99%
“…Due to their inherent and extraordinary physical, chemical, electronic [3,4], and mechanical properties [5], CNTs have raised much interest and provided exciting opportunities for producing advanced materials for new applications [6][7][8][9]. They have fast become one of the most researched topics and interest in different scientific fields such as batteries, hydrogen storage, gas sensors [10], optoelectronic devices [11], and catalysts [12].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the Pd/AC is more active than Pd/CNTs for the aerobic oxidation of cinnamyl alcohol in ethanol. Moreover Karousis et al [14] reported higher activity of CNTs supported metal nanoparticles with respect to AC supported ones in the hydrogenation of methyl-9-octadecenoate and 2-methyl-2-pentenal. They concluded that the high catalytic performance of CNTs supported Pd is due to the large active surface of metallic palladium.…”
Section: Introductionmentioning
confidence: 99%